2019
DOI: 10.1080/13662716.2019.1676704
|View full text |Cite
|
Sign up to set email alerts
|

The four faces of creative industries: visualising the game industry ecosystem in Helsinki and Tokyo

Abstract: Research on creative industries has been gaining momentum during the last few decades with contributions coming from diverse fields. This said, there is a paucity of studies to specify how and why companies in the game industry cluster. In this paper, we inquire into how individuals visualise 2 perceptions of their game industry ecosystem in Helsinki, Finland, and Tokyo, Japan. Tokyo is one of the oldest game industry hotspots, whereas Helsinki has entered the picture only during the 21 st century. Utilising d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 136 publications
(181 reference statements)
0
17
0
Order By: Relevance
“…For example, using the example of Lithuania, Jurene and Jureniene (2017), or Kozina and Bole (2018) using the example of Slovenia have noticed that creative clusters are created in the largest urban centres. Similarly, Lehtonen et al (2020), Murzyn-Kupisz and Działek (2021) and Boix et al (2015) saw the same regularity; the latter found that as many as 75% of creative clusters in the European Union are located in metropolitan areas.…”
Section: Final Conclusionmentioning
confidence: 75%
“…For example, using the example of Lithuania, Jurene and Jureniene (2017), or Kozina and Bole (2018) using the example of Slovenia have noticed that creative clusters are created in the largest urban centres. Similarly, Lehtonen et al (2020), Murzyn-Kupisz and Działek (2021) and Boix et al (2015) saw the same regularity; the latter found that as many as 75% of creative clusters in the European Union are located in metropolitan areas.…”
Section: Final Conclusionmentioning
confidence: 75%
“…In the 1990s, personal computers, laptops and digitalization had begun to take a big chunk of the home console market, enabling ‘hardcore’ or expert users to develop games on their own. By the early 2000s, many games would be technologically advanced, complex and highly sophisticated (Aoyama & Izushi, 2003; Lehtonen et al, 2020). In this context, North American studios as a rule were already specializing in coming up with battle and competition games for which they would be known: Activision Blizzard with Call of Duty, World of Warcraft; Electronic Arts with FIFA, Battlefield, Mass Effect; Take‐Two Interactive with Civilization, NBA 2K series, Grand Theft Auto; ZeniMax Media with Doom, Fallout, The Elder Scrolls and Niantic with Ingress.…”
Section: Resultsmentioning
confidence: 99%
“…While other cultural industries in Finland still address local audiences, most game companies have been forced to design their products for international markets. Since local companies do not operate in the same tiny market, it has been documented that they do not primarily see each other as competitors, but instead actively collaborate and share information with each other (Komulainen & Sotamaa, 2020;Lappalainen, 2014;Lehtonen, Ainamo & Harviainen, 2019).…”
Section: Formation Of the Finnish Game Industrymentioning
confidence: 99%